Familien mit behinderten Angehörigen im Erwachsenenalter Lebensqualität und Lebensperspektiven - Schäfers, Markus (Verlag Julius Klinkhardt, 2024)
Many people with disabilities continue to live with their parents continue to live with their parents or close relatives. This study analyses the living situations of these families. What are their ideas about the future living and care situation of the family member with a disability? At the same time, the study focusses on those families in which the family member with a disability has moved out of the home. What are the reasons for moving out and how do the families experience the transition to assisted living? The findings of the study are used to further develop concepts for family counselling and support.